Liberalizm gospodarczy w myśli Carla Mengera - Mak, Mariusz (Annales. Etyka w Życiu Gospodarczym, 2020)
Over the years, the Austrian School of Economics has created the image of a thinker associated with ideas of liberalism. The views of members of this school are often considered controversial. However, the concept of freedom clearly displayed by the Austrians is very popular among economists. Carl Menger is said to be the founder and a leading member of the Austrian School of Economics, and his works are mostly devoted to methodology and economic theory. Nevertheless, you can also find his views on the sphere of economic liberalism and freedom. Almost 150 years after the publication of Menger’s main works, it emerged that he had created not only the timeless foundations of the theory and methodology of economics, but his theory of subjective value had become the bedrock which is used to this day in deliberations on economic liberalism. The economy pursued by Menger (based primarily on the ideas of subjectivism and individualism) continues to be an important and timeless foundation for the development of the doctrine of economic liberalism. This article is a review based on an analysis of the literature on the subject.